2020
DOI: 10.3390/math9010008
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Study of the Impact of District-Level Characteristics on Texas Student Growth Trajectories on a High-Stakes Math Exam

Abstract: Mathematics is a core content area in the science, technology, engineering, and mathematics (STEM) fields and is vital to student learning in the other STEM subjects. The purpose of this study was to investigate the math performance of fifth- and eighth-grade students in 1170 Texas school districts. We conducted growth hierarchical linear modeling in SAS 9.4 in order to explore the effects of time, district-level characteristics, and their interaction on student performance as measured by the State of Texas As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Disparities in socioeconomic status (SES) can considerably affect the achievement gap between students in rural and non-rural settings [44]. Moreover, English language proficiency is imperative to students' academic success, specifically in reading, math, and science [18,45,46]. Recent research has also established a potent correlation between the teacher turnover rate and student mobility rate, along with their academic performance in diverse subjects [18,45,46].…”
Section: Geographic and Demographic Factors Affecting Academic Perfor...mentioning
confidence: 99%
See 3 more Smart Citations
“…Disparities in socioeconomic status (SES) can considerably affect the achievement gap between students in rural and non-rural settings [44]. Moreover, English language proficiency is imperative to students' academic success, specifically in reading, math, and science [18,45,46]. Recent research has also established a potent correlation between the teacher turnover rate and student mobility rate, along with their academic performance in diverse subjects [18,45,46].…”
Section: Geographic and Demographic Factors Affecting Academic Perfor...mentioning
confidence: 99%
“…Specifically for schools in rural areas, students' learning loss and the possible factors that impacted their achievement might need a close look. For example, compared to non-rural school districts, rural school districts normally had significantly more students identified as economically disadvantaged [17], limited instructional expenditure [18], a higher student mobility rate [17,19], and a high teacher turnover rate [20,21]. Given the geographic isolation of rural schools, limited resources, and lack of support, rural schools face significant challenges in providing effective and quality professional development to teachers [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rural school districts, including the current study context, are reported to have limited state and federal funding to address various school needs (Showalter et al, 2017;Wang et al, 2019;Williams, 2010). These districts normally have significantly low instructional expenditure (Tang et al, 2021b), and high percent of EC students (Strange et al, 2012), student mobility (Paik & Phillips, 2002;Reynolds et al, 2009), and teacher turnover (Lowe, 2006). Students in rural districts demonstrate relatively low academic achievement in reading (Cantrell et al, 2018;Tang et al, 2021a) and science (Holland et al, 2011;Wang et al, 2019) as compared to students in districts serving middleand upper-class population.…”
mentioning
confidence: 99%